Knowledge, attitudes, and practices regarding COVID-19 and mental health status among college students in China: a cross-sectional study - Yi-Hua Li; Tao Wen; Yin-Shi Cui; Zhe-Hu Huang; Yan-Qun Liu; Yan-Qun Liu; Yan-Qun Liu (Frontiers Media S.A., 2023)
BackgroundDuring the prevalence of coronavirus disease 2019 (COVID-19), little was known about the knowledge, attitudes, practices (KAP) about COVID-19 and psychological status of college students in minority areas. This study aimed to evaluate the KAP of college students in minority areas of China toward COVID-19 and to provide a scientific basis for health education and policy formulation.MethodsFrom October 28th to November 6th, 2021, a cross-sectional study was conducted with 5,272 college students to examine KAP and its effects on mental health.ResultsRegarding COVID-19 knowledge, the overall awareness rate was 24.11% (1,271). Regarding health attitudes, most students had positive attitudes about COVID-19 prevention and control (94.95%), and females had higher positive attitudes than males (OR: 1.920; CI: 1.494-2.469). Regarding preventive behaviors, more than half of the students took preventive measures (53.48%), and freshmen had the highest health behavior scores. In terms of psychological status, there were fewer females with depression and stress than males.ConclusionCollege students in minority areas have positive health attitudes; however, their knowledge of COVID-19 prevention and control is low. Moreover, their precautionary behaviors are insufficient, and they have many negative emotions.